Bifacial-metasurface-enabled pancake metalens with polarized space-folding - Chen Chen; Xin Ye; Jiacheng Sun; Yuxin Chen; Chunyu Huang; Xingjian Xiao; Wange Song; Shining Zhu; Tao Li (Optica Publishing Group, 2022)
Replacing traditional refractive lenses with metalenses that have ultrathin and flat architecture could make imaging systems more compact. However, the space between the lens and image is usually the dominating factor in determining the bulkiness, and it cannot be shortened just by using thinner lenses. Here, we propose a pancake metalens that folds the optical path at will using a metacavity consisting of a spin-dependent bifacial metasurface and a mirror. We first verify the asymmetric and independent functions of this bifacial metasurface, and then demonstrate the polarized space-folding effect of the meta-cavity. Imparted with specifically designed phase, we demonstrate a pancake metalens with on- demand (e.g. 2/3, and 4/5) reduction of imaging distance and relatively good imaging performance. This pancake metaoptics framework could enable miniaturization of imaging systems and would provide insights for metadevice applications.
Keywords: Uncategorized